School social work : a direct practice guide - Tuzeo-Jarolmen, JoAnn , 1945- (Sage, 2014)
Offering a unique focus on evidence-based interventions, critical thinking, and diversity, School Social Work prepares you for the realities of working with children and adolescents in schools. Each chapter reviews a basic concept and then provides two in-depth activities you can apply to real world situations. Practical, hands-on experiences, best-practice approaches, and case examples throughout the book show you techniques in action and help you to understand the nuances and complexities of working in a school environment. From collaborating with teachers and parents to dealing with ethical dilemmas and crises, you'll find practical, hands-on coverage you can use as a school social worker.-- Back cover